PENGARUH PROFITABILITAS, SIZE DAN GROWTH TERHADAP STRUKTUR MODAL PADA INDUSTRI BARANG KONSUMSI YANG DIDASARI OLEH PECKING ORDER THEORY DAN TRADE-OFF THEORY - Ika Yustina Rahmawati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2016)
This study aims to determine the effect of profitability, size and growth of the company's capital structure in the consumer goods industry sector based on the pecking order theory and trade-off theory. This research was conducted using the procedure panel data for a sample of 26 consumer goods industry sector companies listed on the Indonesia Stock Exchange during 2009- 2013. The findings of this study is to support H1a, H2b and H3b. based on the results of the analysis of the profitability variable (measured ROE) there is a negative correlation significant at α = 5%, which means supporting the pecking order theory. The size variable (as measured by total assets) and growth (which was measured by the Market to Book Value) positively associated significant at α = 5% and 10%, which means supporting the trade-off theory. For the selection method of FEM and REM, researchers used a test in which the capital REM Test Hausmant be an option for the measurement of capital structure (DER, DAR and Working capital) while FEM selected for the measurement of capital structure (Leverage). Keyword: profitability, size, growth, capital struktur, pecking order theory and trade-off theory